Perawatan Luka Modern dalam Penyembuhan Pasien Diabetic Foot Ulcer: (Literature Review) - Ulfa Lailatul Farkah; Dwi Yogo Budi Prabowo; Hanifah Sahar Al Afra (Institut Nalanda, 2026)
Diabetes Mellitus is a metabolic disorder characterized by impaired carbohydrate metabolism and persistent hyperglycemia resulting from the body's inability to regulate insulin secretion effectively. This condition can lead to various long-term complications associated with abnormalities in protein, fat, and carbohydrate metabolism. One of the chronic complications of Diabetes Mellitus is a diabetic foot ulcer. Modern wound care has emerged as a more effective approach than conventional wound management because it maintains a moist wound environment that promotes healing. This study analyzed the effectiveness of modern wound care in promoting the healing of diabetic foot ulcers. This literature review used a systematic review approach based on the PICO (Population, Intervention, Comparison, Outcome) framework. The inclusion criteria comprised experimental studies published between 2021 and 2025, written in either Indonesian or English, available as original research articles, and accessible in full-text format. The researchers searched for articles in the ScienceDirect, PubMed, ProQuest, and Google Scholar databases and identified 1,502 articles from ScienceDirect, 1,710 from Google Scholar, 13,555 from ProQuest, and 50 from PubMed. After applying the inclusion criteria, the researchers selected 10 articles for review. The review analyzed these articles by identifying similarities and differences, providing critical perspectives, making comparisons, and summarizing the findings. The literature review found that various types of modern dressings, including silver dressings, hydrocolloid dressings, epidermal growth factor-loaded carboxymethylcellulose (EGF-CMC) hydrogel, calcium alginate ZnO nanoparticles, and umbilical cord blood platelet lysate (UCB-PL) gel, effectively promote the healing of diabetic foot ulcers.